2013
DOI: 10.1016/j.agee.2013.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Impact of agronomic practices of an intensive dairy farm on nitrogen concentrations in a karst aquifer in Ireland

Abstract: Exploring the relationship between agricultural nitrogen (N) loading on a dairy farm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 59 publications
(51 reference statements)
3
25
0
Order By: Relevance
“…In addition, the spatial (Peck et al, 1977;Gumiere et al, 2013) and temporal variability (Mapa et al, 1986;Sousa et al, 2013) of weather and soil data and the proximity of a particular landscape position relative to ground and surface water receptors (Jordan et al, 2005;Schulte et al, 2006;Fenton et al, 2008;Fenton et al, 2011;Sousa et al, 2013) are significant when determining the importance of t u . Numerous studies (Foussereau et al, 2001;Baily et al, 2011;Fenton et al, 2011;Gladnyeva and Saifadeen, 2013;Huebsch et al, 2013;Premrov et al, 2014) have identified the critical influence exerted by meteorological patterns on t u . Direct recharge (sometimes called effective drainage -Fenton et al (2011)) to groundwater (and hence contaminant transport and t u ) is implicitly linked with rainfall amount and soil/subsoil/bedrock permeability (Fitzsimons and Misstear et al, 2006).…”
Section: Time Lagmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the spatial (Peck et al, 1977;Gumiere et al, 2013) and temporal variability (Mapa et al, 1986;Sousa et al, 2013) of weather and soil data and the proximity of a particular landscape position relative to ground and surface water receptors (Jordan et al, 2005;Schulte et al, 2006;Fenton et al, 2008;Fenton et al, 2011;Sousa et al, 2013) are significant when determining the importance of t u . Numerous studies (Foussereau et al, 2001;Baily et al, 2011;Fenton et al, 2011;Gladnyeva and Saifadeen, 2013;Huebsch et al, 2013;Premrov et al, 2014) have identified the critical influence exerted by meteorological patterns on t u . Direct recharge (sometimes called effective drainage -Fenton et al (2011)) to groundwater (and hence contaminant transport and t u ) is implicitly linked with rainfall amount and soil/subsoil/bedrock permeability (Fitzsimons and Misstear et al, 2006).…”
Section: Time Lagmentioning
confidence: 99%
“…Furthermore, meteorology and rainfall intensity were shown to play a critical role in determining the rate and nature of solute movement and eventual recharge to groundwater and hence, should be accounted for in numerical models (e.g. Torres et al,1998;Misstear, 2000;Pot et al, 2005;Schulte et al, 2006;Baily et al, 2011;Keim et al, 2012;Kramers et al, 2012;Fenton et al, 2013;Gladnyeva and Saifadeen 2013;Huebsch et al, 2013;Jahangir et al, 2013). By increasing time-step, the user essentially averages precipitation over a greater duration, which poorly reflects the intensity of the event and consequently results in errors in model outputs.…”
Section: Meteorological Data Resolutionmentioning
confidence: 99%
“…Best practice nutrient and agronomic management was applied to the management of each farmlet within the study and has been reported previously by Huebsch et al (2013). Chemical N fertilizer (a combination of urea and calcium ammonium nitrate, depending on the time of year) application rates were common across SR treatments at 250 kg of N/ha per year and were applied according to recommended rates and timings (Teagasc, 2009).…”
Section: Grazing Feeding and Nutrient Managementmentioning
confidence: 99%
“…However, there is vivid evidence of contaminant transport in karst, e.g. of nitrate (Huebsch et al, 2013), herbicides (Hillebrand et al, 2014), fecal bacteria (Pronk et al, 2006), pesticides (Mahler and Massei, 2007) or chloride used as a wastewater indicator .…”
Section: Introductionmentioning
confidence: 98%